Pendugaan Area Kecil Persentase Anak Usia 0-17 Tahun yang Hidup di Bawah Garis Kemiskinan Tingkat Kabupaten/Kota di Pulau Jawa Tahun 2023 - Puspitasari, Dwi Ajeng; Herlan, Mumtahanah Ceisa; Fatah, Saifullah; Sedana Nugraha, I Gusti Ngurah Yogi; Manik, Rizky Wahyuda; Istiana, Nofita; Yuniasih, Aisyah Fitri (Politeknik Statistika STIS, 2024)
Poverty is a problem that continues to confront various countries in the world, with no exception in Indonesia. Poverty reduction is the main focus of the Sustainable Development Goals (SDGs) and the 2020-2024 National Medium-Term Development Plan (RPJMN), with the main focus not only on the poverty of the national population but also the children who live in it. It is known that 47.39 percent, or almost half, of poor children in Indonesia are dominated by Java Island. Therefore, to be able to realize this target, it is necessary to have data availability in small areas, especially areas with a high percentage of poor children on Java Island. This study aims to estimate the percentage of children aged 0-17 years living below the poverty line at the city district level using the Small Area Estimation Hierarchical Bayes (SAE HB) method. Based on the results, estimation using the SAE HB method is able to produce a better Relative Standard Error (RSE) than direct estimation results.